Pathological findings after primary chemotherapy in patients undergoing simultaneous orchidectomy and retroperitoneal lymph node dissection for advanced germ cell tumours. (27th September 2012) - Miller, Rowan E.; Dudderidge, Tim; Huddart, Robert; Seckl, Michael J.; Rustin, Gordon J.S.; Christmas, Timothy J.
Abstract : What's known on the subject? and What does the study add? Testicular cancer is a chemosensitive disease. Treatment with primary chemotherapy leads to eradication of metastatic disease and high cure rates. Completion orchidectomy is usually performed after primary chemotherapy with viable tumour and teratoma often identified in the orchidectomy specimen. The need for completion orchidectomy in patients with a complete response to systemic chemotherapy is uncertain. The present study confirms the discordance in pathology in patients undergoing simultaneous orchidectomy and retroperitoneal lymph node dissection (RPLND) after chemotherapy for metastatic disease. Viable tumour is frequently present in the testis despite tumour‐free RPLNs. These findings support the need for completion orchidectomy as part of the management for advanced testicular germ cell cancer. OBJECTIVE:   To determine the differential response to systemic chemotherapy in patients undergoing simultaneous orchidectomy and retroperitoneal lymph node dissection (RPLND) after chemotherapy for metastatic testicular cancer. PATIENTS AND METHODS:   Patients who underwent simultaneous RPLND and orchidectomy after chemotherapy were identified from our clinical databases.   Postoperative pathological findings and patient characteristics were reviewed. RESULTS:   In all, 42 patients were identified.   After chemotherapy, necrosis, teratoma and cancer were identified in 25 (59.5%), 14 (33.3%) and three (7.1%) RPLN specimens and 15 (35.7%), 15 (35.7%) and 12 (28.6%) orchidectomy specimens respectively.   Of the 25 patients with necrotic RPLN specimens 12 (48.0%) had active disease within the orchidectomy specimen (eight invasive cancer and four mature teratoma).   The overall histological discordance rate was 38.1%. Findings in the orchidectomy specimens were more aggressive than those in the RPLN specimens (i.e. cancer worse than teratoma, which is worse than necrosis) in 33.3%. CONCLUSIONS:   There is significant disparity between orchidectomy and RPLND findings with viable tumour appearing frequently in the testis despite tumour‐free RPLNs.   These findings support completion orchidectomy as part of advanced testicular germ cell treatment.